The prevalence of HIV, hepatitis B, hepatitis C and syphilis infections among blood donors in Hospital Sultanah Nur Zahirah, Kuala Terengganu and its associated risk factors - Daud, Adibah (2020)
Introduction: Blood and blood products transfusion are among the measures used in modern medicine to manage patients, especially those who are anaemic or having significant blood loss. This measure is not without risk, with one of the concerned risk is transfusion transmitted infection (TTI). This study was aimed to determine the prevalence of HIV, hepatitis B (HBV), hepatitis C (HCV) and syphilis infections among blood donors in Hospital Sultanah Nur Zahirah (HSNZ) and the associated risk factors. Methodology: This case control study involved retrospective record review of all blood donors in HSNZ from 2011 until 2017. Seropositive donors were identified based on the positive serological tests. The data of blood donors were extracted from E-delphyn online system. The data on seropositive blood donors were extracted from the SUKUSA online system and donors’ counseling records. For the association of the sociodemographic characteristics and the seropositivity, a group of randomly chosen seronegative blood donors were selected as the control group. Data were analysed using SPSS software version 24. Results: There was a total of 94,989 blood donations in HSNZ from 2011- 2017, with majority of donations were Malays (91.6%), males (66.1%), students (53.4%), repeat donors (61.3%), and were from mobiles collection (84.7%). There was a total of 330 seropositive donations with the prevalence of 0.35%. HBV positivity constituted the highest prevalence (0.171%) followed by HCV (0.113%), syphilis (0.04%), and HIV(0.024%). There were 13 seroconvert donors (0.014%) with the highest seroconversion was seen with HIV infection (5), followed by HCV (4), HBV (3) and syphilis (1). The majority of the identified risk factors among the seropositive blood donors were the unsafe sexual practices (51.7%), followed by having family history (38.3%), IVDU (8.3%) and previous history of transfusion (1.7%). These risk factors showed significant associations with all the TTI (p-values <0.05). The multiple logistic regression analysis showed that the odds of being seropositive were significantly higher in males compared to females, first time donors compared to repeat donors, occupation other than government servants compared to students and donation at mobiles compared to donation at centre respectively (p-values <0.05). Conclusion: The prevalence of seropositive and seroconvert blood donors in HSNZ were low with HBV was the most frequent infection. The most common associated risk factor was the unsafe sexual practice. Being male, first time donors, non-students, and donation at mobiles showed significantly higher risk of seropositivity.